Maternal Benzophenone Exposure Impairs Hippocampus Development and Cognitive Function in Mouse Offspring. Issue 23 (28th October 2021) - Cui, Fengzhen; Pan, Qingfei; Wang, Siyi; Zhao, Faming; Wang, Runxin; Zhang, Tingting; Song, Yaying; He, Jun; Zhang, Haolin; Weng, Qiang; Jin, Yang; Xia, Wei; et al.
Abstract: Benzophenones are widely supplemented in personal care products, but little is known about its neurodevelopmental toxicity. The previous epidemiological study discovered a negative correlation between maternal exposure to a benzophenone metabolite 4‐hydroxybenzophenone (4HBP) and child's neurodevelopment, yet the causal relationship and detailed mechanism remain to be defined. Here, it is reported that prenatal, but not postnatal, exposure to environmentally relevant level of 4HBP impairs hippocampus development and causes cognitive dysfunction in offspring mice. Transcriptomic analyses reveal that 4HBP induces the endoplasmic reticulum stress‐induced apoptotic signaling and inflammatory response in hippocampal neural stem cells. Mechanistically, 4HBP exposure activates protein kinase R‐like ER kinase (PERK) signaling, which induces CHOP, inhibits I κ B translation, and transactivates p65, thereby promoting inflammation and apoptosis on multiple levels. Importantly, genetic or pharmacological inhibition of PERK pathway significantly attenuates 4HBP‐induced NF κ B signaling and neurodevelopmental abnormalities in mice and in a human brain organoid model. The study uncovers the neurodevelopmental toxicity of BP and cautions its exposure during pregnancy. Abstract : This study shows that maternal exposure to benzophenone and its major metabolite 4‐hydroxybenzophenone during pregnancy disrupt endoplasmic reticulum proteostasis and trigger inflammation in the offspring hippocampal neural stem cells, leading to cognitive dysfunction and neurodevelopmental toxicity. This phenomenon can be greatly ameliorated by inhibiting the protein kinase R‐like ER kinase signaling of the unfolded protein response.